Kaufman's clinical neurology for psychiatrists - Kaufman, David Myland; ScienceDirect eBooks (London : Saunders/Elsevier, 2013)
"Completely revised in response to the new format of the ABPN certifying exam, Kaufman's Clinical Neurology for Psychiatrists is the ideal reference to enhance your mastery of the neurology knowledge needed for the Psychiatry Board exam. Nearly 2,000 multiple-choice practice questions, in print and online, assess your familiarity with the latest topics in the field! Enhance your mastery of the material with the help of abundant line drawings, CTs, MRIs, and EEGs that demonstrate key clinical findings to facilitate diagnosis. Fully understand each condition's relevant history, neurologic and psychiatric features, easily performed office and bedside examinations, appropriate tests, differential diagnosis, and management options"--Publisher's description.
Sect. I. Classic anatomic neurology -- 1. First encounter with a patient : examination and formulation -- 2. Central nervous system disorders -- 3. Psychogenic neurologic deficits -- 4. Cranial nerve impairments -- 5. Peripheral nerve disorders -- 6. Muscle disorders -- Sect. II. Major neurologic symptoms -- 7. Dementia -- 8. Aphasia and related disorders -- 9. Headaches -- 10. Epilepsy -- 11. TIAs and strokes -- 12. Visual disturbances -- 13. Congenital cerebral impairments -- 14. Neurological aspects of chronic pain -- 15. Multiple sclerosis episodes -- 16. Neurologic aspects of sexual function -- 17. Sleep disorders -- 18. Involuntary movement disorders -- 19. Brain tumors and metastatic cancer -- 20. Lumbar puncture and imaging studies -- 21. Neurotransmitters and drug abuse -- 22. Traumatic brain injury -- App. 1. Patient and family support groups -- App. 2. Costs of various tests and treatments -- App. 3. Diseases transmitted by chromosomes or mitochondria abnormalities -- App. 4. Chemical and biological neurotexins -- App. 5. Three nonethanol toxic alcohols -- Additional review questions and answers.
Previous edition: 2006.
Includes bibliographical references and index.
Online resource; title from resource home page (ebrary, viewed January 20, 2016).
Elsevier
Elsevier
Keywords: Nervous system -- Diseases; Neurology; Psychiatrists; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Nervous system -- Diseases; Neurology; Psychiatrists; Nervous System Diseases -- diagnosis; Diagnosis, Differential; Psychiatry -- methods; Electronic books